Crouzon Syndrome: Diagnosis, treatment and its clinical correlations (Research, Society and Development, 2023)
Crouzon syndrome is a hereditary primary craniofacial alteration, with autosomal dominant transmission with a wide phenotypic variety, characterized by premature closure of cranial sutures leading to loss of plasticity in the developing skull. The most evident clinical signs of this alteration are: Hypertelorism, exophthalmos, hooked nose or "parrot beak nose" and mandibular prognathism. That said, an early and multidisciplinary approach with a specific schematic prognosis is extremely necessary. Therefore, the objective of this literature review is not only to describe this alteration in detail, but also to inform the main and most common forms of diagnosis and treatments in several different areas. To obtain the necessary data, a bibliographic search was carried out in the PUBMED databases with the MeSH descriptors: “Crouzon Syndrome”, "Craniofacial characteristics in Crouzon's syndrome", "Prevalence of Ocular Anomalies in Craniosynostosis" being combined through the Boolean operator "AND " and SCIELO with the keyword "Syndromic craniosynostosis". Only original articles were included, in Portuguese, English and Spanish, between 1982 and 2023. In total, 482 studies were found, but only 30 were selected through the inclusion criteria. Studies show that Crouzon Syndrome demands multidisciplinary management, in which the interaction between the vast majority of health professionals is extremely important, contributing to an early diagnosis and specific management, always aiming to promote an individualized treatment, providing quality of life to these patients.